Flies kNOw How to Signal. - Silverman, N. (Developmental Cell, 2003)
A recent study has discovered a surprising role for nitric oxide in the Drosophila immune response. NO-mediated signaling was implicated in the communication between the site of a localized infection and the major immune organ of the fly, the fat body.